2021
DOI: 10.3389/fimmu.2021.689397
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between CD11b and Piezo1 Mediates Macrophage Responses to Mechanical Cues

Abstract: Macrophages are versatile cells of the innate immune system that perform diverse functions by responding to dynamic changes in their microenvironment. While the effects of soluble cues, including cytokines and chemokines, have been widely studied, the effects of physical cues, including mechanical stimuli, in regulating macrophage form and function are less well understood. In this study, we examined the effects of static and cyclic uniaxial stretch on macrophage inflammatory and healing activation. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 58 publications
(113 reference statements)
1
39
0
Order By: Relevance
“…Macrophages are sensitive to mechanical stimuli, and affect their biological behavior by converting mechanical signals into cellular messages depending on various mechanosensors 30 . Mechanosensitive ion channels mediated Ca 2+ influx has been identified as a key second messenger in macrophage polarization 14,31 . The reduction of alveolar surface tension in vivo could regulate the shape of cells and increase the phagocytic activity of alveolar macrophages 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are sensitive to mechanical stimuli, and affect their biological behavior by converting mechanical signals into cellular messages depending on various mechanosensors 30 . Mechanosensitive ion channels mediated Ca 2+ influx has been identified as a key second messenger in macrophage polarization 14,31 . The reduction of alveolar surface tension in vivo could regulate the shape of cells and increase the phagocytic activity of alveolar macrophages 32 .…”
Section: Discussionmentioning
confidence: 99%
“…84 In addition, a recent study demonstrated that there is a synergy between cellular mechanotransduction and biochemical signals in the regulation of macrophages which would be related to CD11b and Piezo1 crosstalk. 85 In this context it has been proposed that shockwave-induced immunomodulation has potential as a non-invasive physical therapy to regulate macrophage functions linked with wound healing 86 and osseointegration. 78,79,87 This could be a biological mechanism behind the re-fixation of orthopedic implants.…”
Section: Strategies Focused On the Peri-implant Osteoimmunology Of Th...mentioning
confidence: 99%
“…It has recently been proposed that mechanical stimulation could promote the conversion of myeloid‐derived monocytes into an activated status, suggesting that occlusal force might determine the immune microenvironment of the alveolar bone 84 . In addition, a recent study demonstrated that there is a synergy between cellular mechano‐transduction and biochemical signals in the regulation of macrophages which would be related to CD11b and Piezo1 crosstalk 85 . In this context it has been proposed that shockwave‐induced immunomodulation has potential as a non‐invasive physical therapy to regulate macrophage functions linked with wound healing 86 and osseointegration 78,79,87 .…”
Section: Immune‐centered Therapeutic Approaches For Clinical Improvem...mentioning
confidence: 99%
“…Finally, a novel mechanically-activated cation channel Piezo1 has been reported in macrophages. Piezo1 roles are proposed to include mechanical stimuli sensing, potentially via Piezo1 and integrins crosstalk and modulation of macrophage polarization ( Atcha et al, 2021a ; Atcha et al, 2021b ), toll-like receptor 4-mediated enhancement of macrophage bactericidal activity ( Geng et al, 2021 ) and macrophage migration (unpublished data). Recently, this channel has also been demonstrated to be a key regulator of erythrocyte phagocytosis by macrophages and iron metabolism ( Ma et al, 2021 ).…”
Section: Further Macrophage Ion Channelsmentioning
confidence: 99%